Dampak Implementasi Sistem Just In Time terhadap Efisiensi Biaya dan Produktivitas Tenaga Kerja pada Usaha Penggilingan Padi Skala UKM (Studi Kasus UD. Suka Kerja) - Dian Fahira; Ravika Mutiara Savitrah (Owner : Riset dan Jurnal Akuntansi, 2026)
Business competition requires firms to improve productivity and efficiency to remain competitive. One strategy that can be adopted is the Just In Time (JIT) system, which emphasizes demand-based production and inventory minimization. This study analyzes the implementation of JIT and its impact on cost efficiency and labor productivity at UD. Suka Kerja, a small and medium-sized rice milling enterprise. Prior studies on JIT largely focus on large-scale manufacturing firms and operational efficiency, while empirical evidence on partial JIT implementation in SMEs, particularly its implications for labor productivity, cost control, and worker welfare, remains limited. This study employs a qualitative case study approach supported by quantitative performance analysis. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana with triangulation of sources and techniques. The findings indicate that although JIT implementation at UD. Suka Kerja remains partial and transitional, as reflected by residual inventory from previous periods and workflow adjustments, it has contributed positively to operational performance. Total production costs decreased by 1.35%, production cost productivity increased from 0.0000671 kg/IDR to 0.0000714 kg/IDR, and production efficiency reached 104.9% relative to the pre-JIT standard. In addition, working hours were reduced by 27.2%, resulting in a 32% increase in labor productivity. Cost control contributed dominantly to profit growth, accounting for 84.49% of the increase in net profit. However, these performance improvements were accompanied by social trade-offs, particularly reduced working hours and worker income, which affected labor acceptance of the JIT system. The findings suggest that while JIT enhances efficiency and financial performance in SMEs, its successful implementation requires alignment with human resource management policies to ensure balanced outcomes between operational efficiency and worker welfare.